Craniofacial phenotypes associated with Robinow syndrome. - Conlon, Christopher J; Abu-Ghname, Amjed; Raghuram, Anjali C; Davis, Matthew J; Guillen, Diana E; Sutton, V Reid; Carvalho, Claudia M B; Maricevich, Renata S (Am J Med Genet A, 2020)
Robinow syndrome is characterized by mesomelic limb shortening, hemivertebrae, and genital hypoplasia. Due to low prevalence and considerable phenotypic variability, it has been challenging to definitively characterize features of Robinow syndrome. While craniofacial abnormalities associated with Robinow syndrome have been broadly described, there is a lack of detailed descriptions of genotype-specific phenotypic craniofacial features. Patients with Robinow syndrome were invited for a multidisciplinary evaluation conducted by specialist physicians at our institution. A focused assessment of the craniofacial manifestations was performed by a single expert examiner using clinical examination and standard photographic images. A total of 13 patients with clinical and molecular diagnoses consistent with either dominant Robinow syndrome (DRS) or recessive Robinow syndrome (RRS) were evaluated. On craniofacial examination, gingival hyperplasia was nearly ubiquitous in all patients. Orbital hypertelorism, a short nose with anteverted and flared nares, a triangular mouth with a long philtrum, cleft palate, macrocephaly, and frontal bossing were not observed in all individuals but affected individuals with both DRS and RRS. Other anomalies were more selective in their distribution in this patient cohort. We present a comprehensive analysis of the craniofacial findings in patients with Robinow Syndrome, describing associated morphological features and correlating phenotypic manifestations to underlying genotype in a manner relevant for early recognition and focused evaluation of these patients.

Extremity anomalies associated with Robinow syndrome. - Abu-Ghname, Amjed; Trost, Jeffrey; Davis, Matthew J; Sutton, V Reid; Zhang, Chaofan; Guillen, Diana E; Carvalho, Claudia M B; Maricevich, Renata S (Am J Med Genet A, 2020)
Robinow syndrome, a rare genetic disorder, is characterized by skeletal dysplasia with, among other anomalies, extremity and hand anomalies. There is locus heterogeneity and both dominant and recessive inheritance. A detailed description of associated extremity and hand anomalies does not currently exist due to the rarity of this syndrome. This study seeks to document the hand anomalies present in Robinow syndrome to allow for improved rates of timely and accurate diagnosis. A focused assessment of the extremities and stature was performed using clinical examination and standard photographic images. A total of 13 patients with clinical and molecular diagnosis consistent with dominant Robinow syndrome or recessive Robinow syndrome were evaluated. All patients had limb shortening, the most common of which was mesomelia; however, rhizomelia and micromelia were also seen. These findings are relevant to clinical characterization, particularly as Robinow syndrome has classically been defined as a "mesomelic disorder." A total of eight distinct hand anomalies were identified in 12 patients with both autosomal recessive and dominant forms of Robinow syndrome. One patient did not present with any hand differences. The most common hand findings included brachydactyly, broad thumbs, and clinodactyly. A thorough understanding of the breadth of Robinow syndrome-associated extremity and hand anomalies can aid in early patient identification, improving rates of timely diagnosis and allowing for proactive management of sequelae.